Dacryocystocele (mucocele of the lacrimal sac). - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
The tears enter the lacrimal dots, run through the intrapalpebral lacrimal canaliculi and merge into the lacrimal sac. The latter is about 12 millimeters long and located beneath the medial palpebral commissura. The lowest extremity of the sac continues in the naso-lacrimal duct, that crosses the facial bones and opens onto the nasal cavity beneath the lower turbinate bone. The obstruction of the lacrimal system occurs more frequently due to a persistent membrane located on the distal extremity of the naso-lacrimal duct (4). Lacrimation, deposition of mucus in the lacrimal sac with consequent bacterial proliferation and tumefaction of the sac follow the obstruction. An acute, abscess infection of the sac may follow. Treatment. In the mild cases, which are more frequent, antibiotic eyedrops three times a day, followed by massage of the lacrimal sac and duct, are enough. In case of acute infection, systemic antibiotics should be added. When the obstruction does not resolve spontaneously, as occurring in most cases within the first 6-12 months of age, an exploration with a probe under general anesthesia should be performed (1, 3).